Reclassifying bioterrorism risk: Are we preparing for the proper pathogens? - Georgios Pappas; Paraskevi Panagopoulou; Nikolaos Akritidis (Elsevier, 2009)
Summary: Existing classifications of potential biological weapons, acknowledge only limited important parameters of biological weapon potential. Certain pathogen factors would further influence the outcome of a potential attack in context with social and political aspects of the time and space of the attack. The importance of these factors was investigated through various attack scenarios that have been developed by the authors, and an individual score for each of these factors was calculated, based on the overall effect their variation had in the scenario outcome. A new classification score for potential biological weapons was subsequently developed, one, which drastically alters the perception of risk for certain pathogens, such as filoviruses and anthrax. This frame further allows for more accurate evaluation of the bioweapon potential of agents such as avian flu. Recognition of intervening factors and proper assessment of the actual risk might augment in proper distribution of interest and funds on relevant medical research. Keywords: Bioterrorism, Risk, Classification